Sinergi Pendidikan dan Masyarakat: Implementasi Administrasi Hubungan Sekolah dan Masyarakat di Era Digital - Anwar Ibrahim; Rehan Aidil; Ahmad Sabri; Rully Hidayatullah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The rapid development of information and communication technology (ICT) has fundamentally changed the educational landscape. Schools, which were previously often considered as stand-alone entities, are now increasingly recognized as an integral part of wider social systems. In this context, the active role of society in the education process becomes increasingly crucial. This research aims to examine in depth how the administration of school and community relations is implemented in the digital era, as well as identifying factors that support or hinder its success. In the last few decades, there has been a paradigm shift in the understanding of education. Education is no longer solely seen as a process of transferring knowledge from teacher to student, but rather as a holistic individual development effort. Society, as a social environment where individuals grow and develop, has a very significant role in shaping the character and competence of students. Therefore, building strong and synergistic relationships between schools and society is the key to realizing quality education that is relevant to the needs of the times. This research has the main aim of analyzing, identifying, evaluating, identifying matters relating to school and community relations. This research uses a literature review approach. Research data was obtained from various sources, including scientific journals, popular articles, research reports, and relevant policy documents. Data analysis was carried out systematically by identifying main themes, comparing findings from various sources, and drawing conclusions based on existing evidence. The research results show that the implementation of administration of school and community relations in the digital era has experienced rapid development. The use of social media platforms, school websites, and mobile applications has facilitated more effective communication between schools and the community. In addition, many schools have involved the community in various school activities, such as extracurricular activities, personal development programs, and decision making regarding school policies.